10-year survival outcome after clinically suspected acute myocarditis in adults: A nationwide study in the pre-COVID-19 era. - Mi-Jeong Kim; Hae Ok Jung; Hoseob Kim; Yoonjong Bae; So Young Lee; Doo Soo Jeon (PLoS ONE, 2023)
Background Clinical courses of acute myocarditis are heterogeneous in populations and geographic regions. There is a dearth of long-term outcomes data for acute myocarditis prior to the coronavirus disease pandemic, particularly in the older and female population. This study aimed to provide the nationwide epidemiologic approximates of clinically suspected acute myocarditis across adults of all ages over the long term. Methods From the nationwide governmental health insurance database, a retrospective cohort comprised all patients aged 20-79 who were hospitalized for clinically suspected acute myocarditis without underlying cardiac diseases from 2006 to 2018. The complicated phenotype was defined as requiring hemodynamic or major organ support. Over 10 years, all-cause mortality and index event-driven excess mortality were evaluated according to young-adult (20-39 years), mid-life (40-59 years), and older-adult (60-79 years) age groups. Results Among 2,988 patients (51.0±16.9 years, 46.2% women), 362 (12.1%) were of complicated phenotype. Of these, 163 (45.0%) had died within 1 month. All-cause death at 30 days occurred in 40 (4.7%), 52 (4.8%), and 105 (10.0%) patients in the young-adult, mid-life, and older-adult groups, respectively. For 10 years of follow-up, all-cause death occurred in 762 (25.5%). Even in young adult patients with non-complicated phenotypes, excess mortality remained higher compared to the general population. Conclusion In hospitalized patients with clinically suspected acute myocarditis, short-term mortality is high both in young and older adults, particularly those with comorbidities and severe clinical presentation. Furthermore, excess mortality remains high for at least 10 years after index hospitalization in young adults.